Identification of the essence of intelligence in problem solving based on pragmaticism’s theory of inquiry / Safawi Abdul Rahman - Abdul Rahman, Safawi (Institute of Graduate Studies, UiTM, 2017)
In Artificial Intelligence (AI), the issue of the essence of intelligence is disputable in which this issue leads to the difficulty in understanding the intelligence. This research enters the challenge of identifying the essence of intelligence by re-visiting the tenet of intelligent behavior due to that intelligent behavior is amenable to reflect intelligence. The investigation into the intelligent behavior leads to the finding that the process and intelligent process are the underpinning principle of behavior. The research progresses to identify the intelligent processes that are said to be truly intelligent. As a result, the problem solving processes are found to be essential source for intelligent processes because problem solving is the key for intelligence. By disregarding the existing problem solving frameworks, this study explores the Pragmaticism’s theory of inquiry, a general philosophical idea that penetrated many academic realms such as in AI since 1950s. The re-exploration of Pragmaticims’s abduction, deduction and induction yields seven intelligent processes namely invention, selection, entertainment, analysis, demonstration, operation and justification…